2009
DOI: 10.1108/13665620910996188
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of trajectories: a newcomer in a community of practice

Abstract: Purpose -The purpose of this paper is to provide a case study of a newcomer to the practice of policing to explore conceptualisations of learning through practice. It aims to position learning as the intersections of trajectories of being and becoming within a community of practice. The paper seeks to argue that learners need to be understood with respect to their personal histories and how these interact with the social and cultural dimensions of the workplace. Design/methodology/approach -This paper is a cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
0
21
1
Order By: Relevance
“…Unlike previous research on the professional learning of police (Campbell et al , 2009; Harris et al , 2004; Lundin and Nulden, 2007) participants in this study indicated that their workplace learning was sharp and immersive, more akin to “being flung in the deep end” [of a swimming pool] than gradually developing skill. Officers reported two reasons for this feeling of unpreparedness: lack of specific curriculum on rural policing, and professional development practices that were impacted by geographic isolation and inclement weather.…”
Section: Professional Learning: “Flung In the Deep End”contrasting
confidence: 96%
See 2 more Smart Citations
“…Unlike previous research on the professional learning of police (Campbell et al , 2009; Harris et al , 2004; Lundin and Nulden, 2007) participants in this study indicated that their workplace learning was sharp and immersive, more akin to “being flung in the deep end” [of a swimming pool] than gradually developing skill. Officers reported two reasons for this feeling of unpreparedness: lack of specific curriculum on rural policing, and professional development practices that were impacted by geographic isolation and inclement weather.…”
Section: Professional Learning: “Flung In the Deep End”contrasting
confidence: 96%
“…Campbell et al (2009) utilise CoP theory to examine the learning trajectory of police probationers in Australia. Drawing on qualitative critical case methodology, they argue that while a newcomer is unknown to the particular community, they enter as a person with experience in the world.…”
Section: Understanding the Professional Learning Of Emergency Service Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In difficult situations, a pep talk from a superior manager was seen as self-reinforcing encouragement to solve tasks independently, which boosted self-confidence. Overall, social support seemed to make it easier to find appropriate solutions to support managers' learning (Billett 2004;Evans et al 2006), form alliances with established managers (Fox 2000), and achieve a legitimate position in the workplace community (Campbell et al 2009;Gardiner 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Access to learning is therefore also dependent on individual-related conditions such as age and gender, and dispositions (Evans et al 2006) or personal epistemologies (Billett 2009) describing each person's specific experiences, such as previous education, employment and professional knowledge. Individuals' dispositions can motivate what they do, what they strategically choose to engage in (Billett 2009), their own initiatives for learning (Akre and Ludvigsen 1997) and their use of learning invitations from experienced colleagues (Billett 2001(Billett , 2004Campbell et al 2009). Individuals' prior knowledge of a workplace's (material and cultural) history facilitates their understanding of the workplace (Campbell et al 2009), their willingness to participate in provided learning situations (Eberle et al 2014) and their learning of the professional language (Gardiner 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%